1995
DOI: 10.1073/pnas.92.22.10257
|View full text |Cite
|
Sign up to set email alerts
|

Proteolysis of major histocompatibility complex class II-associated invariant chain is regulated by the alternatively spliced gene product, p41.

Abstract: Invariant chain (Ii) is an intracellular type II transmembrane glycoprotein that is associated with major histocompatibility complex class II molecules during biosynthesis. Ii (5,7,8).Once the class 11-Ii complexes arrive in endosomes, Ii appears to be degraded through the generation of a nested set of amino-terminal fragments, some of which remain transiently associated with class II (9-11). The ability of Ii to enhance the localization of class II to endosomes has been mapped predominantly to a region in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

1996
1996
2004
2004

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 53 publications
(39 reference statements)
1
21
0
Order By: Relevance
“…To explain this differential sensitivity to proteases, the authors offered two possibilities: either the C-terminus (containing the Tg type-1 module) of P41 induces conformational changes which could alter the configuration of protease-sensitive sites, or released P41-specific fragments directly change the specificity or efficiency of endosomal proteases. These results show that a protein containing a Tg type-1 module is both capable of binding a protease [18] and of specifically controlling some of the proteolytic events that the protein containing the module undergoes [19].…”
Section: Cathepsin L Is Reversibly Complexed and Inhibited By Thementioning
confidence: 76%
See 1 more Smart Citation
“…To explain this differential sensitivity to proteases, the authors offered two possibilities: either the C-terminus (containing the Tg type-1 module) of P41 induces conformational changes which could alter the configuration of protease-sensitive sites, or released P41-specific fragments directly change the specificity or efficiency of endosomal proteases. These results show that a protein containing a Tg type-1 module is both capable of binding a protease [18] and of specifically controlling some of the proteolytic events that the protein containing the module undergoes [19].…”
Section: Cathepsin L Is Reversibly Complexed and Inhibited By Thementioning
confidence: 76%
“…Two facts argue for a possible role of the Tg type-1 module in Ii degradation mechanisms. First, Ogrinc et al [18] showed that the C-terminal part of P41 (containing the Tg type-1 module) is able to reversibly and specifically inhibit and stabilize cathepsin L in a pH-dependent manner; second, Fineschi et al [19] proved that P31 and P41 have different patterns of proteolytic processing. Therefore, in transfected cells expressing only the P41 form of Ii, degradation of P41 generates a 12 kDa N-terminal fragment of Ii (P12) that remains associated with MHC class II for an extended time; in contrast, when P31 is expressed alone it is subjected to extensive degradation without an intermediate fragment associated with MHC class II.…”
Section: Cathepsin L Is Reversibly Complexed and Inhibited By Thementioning
confidence: 99%
“…Morphological studies have shown that intracellular vesicles staining for Ii are enriched with endocytic markers, but also with late endosomal or lysosomal markers such as cation-independent M6P-R [49,50]. Once the (~Ii)a complexes arrive in endosomes, Ii is proteolytically degraded leading to the generation of N-terminal fragments, some of which remain transiently associated with class II molecules [51,52]. Complexes of ~13 with a set of 20-24 residue Ii fragments called CLIP (class II associated invariant chain peptide) have been identified as intermediates in class II molecule maturation [53].…”
Section: Endosomal Proteolysis Of Antigens For Mhc-ii Presentationmentioning
confidence: 99%
“…The CLIP segment, which likely binds to the ~13 binding site in a way almost identical to that in which antigenic peptides bind MHC-II molecules [53], is necessary for in vivo Ii activity ]54]. Proteolytic events also generate a 12 kDa N-terminal fragment of Ii which does not include the CLIP region of Ii and which remains associated with class II molecules for an extended period of time [51].…”
Section: Endosomal Proteolysis Of Antigens For Mhc-ii Presentationmentioning
confidence: 99%
“…Thus far, we have not been able to demonstrate such interactions in detergent extracts of mEGP-expressing DCs, and we observe no cocapping of mEGP and MHC class II molecules on the surface of DC (not shown), providing further evidence against a direct interaction in vivo. Additionally, in contrast to p41 for which the thyroglobulin-like domain inhibits cathepsin L activity in vitro and in vivo (61)(62)(63), expression of mEGP does not inhibit DC cathepsin L or S activity in in vitro assays (data not shown). Indirect effects of mEGP on MHC class II complex function or APC/T cell interactions are thus more likely to explain the inhibition of Ag presentation.…”
Section: Discussionmentioning
confidence: 99%